1981
DOI: 10.1016/s0140-6736(81)91851-1
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Cyclosporin a in Liver and Kidney Transplant Patients

Abstract: SummaryIn six of twelve orthotopic liver recipients nephrotoxicity was noted after 13-22 days of treatment with 16.3±2.9 (SEM) mg/kg per day of cyclosporin A (CyA). With a decrease in the daily CyA dose to 9.2±2.3 (SEM) mg/kg kidney function returned to normal. No hepatic rejections occurred on this lowered CyA dose. In 4 out of 66 kidney recipients a switch from a CyA dose of 5.2-10.7 mg/kg daily to azathioprine was done 4-8 months after transplant because of unsatisfactory kidney function, suspected to be du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(44 citation statements)
references
References 4 publications
1
42
0
1
Order By: Relevance
“…However, its use is limited by significant adverse side effects, in particular, acute and chronic calcineurin inhibitor nephrotoxicity [38,39] and high variety in bioavailability, which can range from 5% to 89% [40] . Because cyclosporine A has a narrow therapeutic index and marked interindividual pharmacokinetic variation, its usage requires monitoring the drug concentration to ensure that it is within the recommended therapeutic range.…”
Section: Cyclosporine Amentioning
confidence: 99%
“…However, its use is limited by significant adverse side effects, in particular, acute and chronic calcineurin inhibitor nephrotoxicity [38,39] and high variety in bioavailability, which can range from 5% to 89% [40] . Because cyclosporine A has a narrow therapeutic index and marked interindividual pharmacokinetic variation, its usage requires monitoring the drug concentration to ensure that it is within the recommended therapeutic range.…”
Section: Cyclosporine Amentioning
confidence: 99%
“…Cyd osporine was administered for 16 weeks at the end of which it was tlisco ntinucd witho ut tapering. The 16 week period was chosen following the design and results of previous C rohn's d isease studies ( 1,23) and because o f the known reversihiliry of renal sitle effects after sho rt term use of cyclosporinc (24,25). Patients were seen regularl y during and after cyclosporinc therapy and their C ro hn's disease course to relapse d ocumented.…”
Section: Materials and Met Hodsmentioning
confidence: 99%
“…In retrospect, part of the problem was failure to distinguish rejection from drug toxicity. 29 Nevertheless, many subsequent reports, including our own, 29,35,36 have shown that nephrotoxicity is the most limiting side effect of cyclosporine.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 89%
“…In retrospect, part of the problem was failure to distinguish rejection from drug toxicity. 29 Nevertheless, many subsequent reports, including our own, 29,35,36 have shown that nephrotoxicity is the most limiting side effect of cyclosporine.The full exploitation of the drug was not possible without combining it with other agents, of which prednisone was the most important. 29,36 By this polypharmacy approach, it was possible to control rejection better even though smaller and less nephrotoxic doses of cyclosporine were used.…”
mentioning
confidence: 89%